Tingkat kemampuan guru dalam menyusun RPP kurikulum merdeka berkarakter: Ditinjau melalui pelatihan dan pendampingan terprogram - Nurlelawati, Nurlelawati (Aksara: Jurnal Bahasa dan Sastra, 2023)
This study aims to improve the ability of teachers in the preparation of learning implementation plans. This research uses the form of school research action research (PTS) which is carried out in 3 (three) cycles, carried out in 2 Bandar Lampung City Assisted Junior High Schools with the subject of research for all teachers in semester 2 of the 2021/2022 Academic Year totaling 20 people. The research method uses School Action Research. Data collection is carried out through observation, interviews and tests. Data analysis is carried out with 3 (three) stages including: data reduction, data presentation and drawing conclusions or verification. The hypothesis states that through the application of programmatic training and assistance, it can improve the ability of teachers in the preparation of learning implementation plans in 2 junior high schools assisted by Bandar Lampung City for the 2021/2022 Academic Year. Empirical data shows that coaching with programmatic training and assisted assistance can improve the ability of teachers of 2 junior high schools assisted by Bandar Lampung City in semester 2 of the 2022/2023 Academic Year in the preparation of a learning implementation plan from the initial condition of the teacher ability value of 63.16 in cycle III to 78.47. So it can be concluded that through the application of training and programmatic assistance, it can improve the ability of teachers to formulate a learning implementation plan.Keywords: teacher ability, lesson implementation plan, training, programmatic mentoring